Healthy planet healthy people. Issue 3 (19th January 2022) - Redford, Kent H.; da Fonseca, Gustavo A.B.; Gascon, Claude; Rodriguez, Carlos Manuel; Adams, Jonathan; Andelman, Sandy; Barron, David H.; Batmanian, Garo; Bierbaum, Rosina; Daszak, Peter; Daugherty, Christine; Griffin, Jeffrey; et al.
Abstract: One Health is a cross‐sectoral and transdisciplinary approach that emphasizes the fundamental ways in which the health of humans, domestic and wild animals, fungi, plants, microbes, and natural and built ecosystems are interdependent. One Health approaches recognize the links between human health and a range of environmental concerns including biodiversity, climate, freshwater, food, harmful chemicals, and healthy oceans. Yet the conservation community and its broad interest in biodiversity and the natural world has been notably lacking in discussions about One Health. Partly as a result, both policy and practice have been narrowly focused on one or a few links between human and other healths, such as the human and wildlife health nexus. We provide a set of principles and components that will balance existing discussions by including the natural world and biodiversity and provide a framework for more active involvement by the conservation community. Incorporating these principles and components will enable One Health practice to guide inclusive, multidisciplinary, and cross‐sectoral efforts that consider the shared costs and benefits of human, animal, plant, and ecosystem health and help readjust humanity's pursuit of a green, just, and equitable sustainability pathway.